Safety and efficacy of chloral hydrate for conscious sedation of infants in the pediatric cardiovascular intensive care unit. Issue 1 (January 2017) - Chen, Mei-Lian; Chen, Qiang; Xu, Fan; Zhang, Jia-Xin; Su, Xiao-Ying; Tu, Xiao-Zhen
Abstract : Abstract: This study evaluates the safety and efficacy of chloral hydrate administration for the conscious sedation of infants in the pediatric cardiovascular intensive care unit (PCICU). We conducted a retrospective review of the charts of 165 infants with congenital heart disease who received chloral hydrate in our PCICU between January 2014 and December 2014. Chloral hydrate was administered orally or rectally to infants using doses of 50 mg/kg. We collected and analyzed relevant clinical parameters. The overall length of time to achieve sedation was ranged from 5 to 35 min (10.8 ± 6.2 min); the overall mean duration of sedation was ranged from 15 to 60 min (33.5 ± 11.3 min); and the overall mean length of time to return to normal activity was 10 min to 6 h (34.3 ± 16.2 min). The length of the PCICU stay was ranged from 3 to 30 days (8.2 ± 7.1 days). Physiologically, there were no clinically significant changes in heart rate, mean arterial pressure, respiratory rate, or peripheral oxygen saturation before, during, or after use of the chloral hydrate. There were no significant differences regarding sedative effects in the subgroups (cyanotic vs acyanotic group, with pulmonary infection vs without pulmonary infection group, and with pulmonary hypertension vs without pulmonary hypertension group). Our experience suggests that chloral hydrate is a safe and efficacious agent for conscious sedation of infants in the PCICU. Abstract : Supplemental Digital Content is available in the text